Implementation of the IT-Based Independent Learning Curriculum in the IPAS Subject at Muhammadiyah Islamic Primary School Karangwaru - Rochmawan, Alfian Eko; Hidayah, Nur; Mutamimah, Umi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2025)
This study aims to examine the implementation of the Independent Curriculum based on Information Technology (IT) in the subject of IPAS (Natural and Social Sciences) at Muhammadiyah Karangwaru Islamic Elementary School , located in Karangwaru Village, Plupuh District, Sragen Regency. The primary focus of this research is to assess the extent to which the integration of IT within the Independent Curriculum enhances the meaningfulness of the IPAS learning process. The research problem is formulated as follows: To what extent does the implementation of the IT-based Independent Curriculum influence the meaningfulness of IPAS learning at Muhammadiyah Karangwaru Islamic Elementary School? The methodology employed is a quantitative descriptive approach, with data collected through closed questionnaires distributed to the head of the madrasa and teacher. The results indicate that a significant majority of respondents hold a positive perception of the implementation of this curriculum. Specifically, 28. 6% of respondents reported that IT-based IPAS learning often provides meaningful learning experiences, while another 28. 6% affirmed that such experiences consistently occur. Conversely, only 14. 3% indicated that they seldom encounter meaningful learning, and another 14. 3% reported never having such experiences. These findings suggest that the application of the IT-based Independent Curriculum can create a more contextual, interactive, and relevant IPAS learning experience. This study contributes to the development of literature on digital education innovation in elementary Islamic education institutions and provides empirical foundations for policymakers and teacher in designing technology-based learning strategies.Penelitian ini bertujuan untuk mengkaji implementasi Kurikulum Merdeka berbasis Teknologi Informasi (TI) pada mata pelajaran IPAS (Ilmu Pengetahuan Alam dan Sosial) di Muhammadiyah Karangwaru Islamic Elementary School , Desa Karangwaru, Kecamatan Plupuh, Kabupaten Sragen. Fokus utama penelitian ini adalah untuk mengetahui sejauh mana integrasi TI dalam Kurikulum Merdeka dapat meningkatkan kebermaknaan proses pembelajaran IPAS. Rumusan masalah dalam penelitian ini adalah: Sejauh mana implementasi Kurikulum Merdeka berbasis TI memberikan dampak terhadap kebermaknaan pembelajaran IPAS di Muhammadiyah Karangwaru Islamic Elementary School ? Metode yang digunakan adalah pendekatan deskriptif kuantitatif, dengan pengumpulan data melalui angket tertutup yang disebarkan kepada kepala madrasah dan tenaga pendidik. Hasil penelitian menunjukkan bahwa sebagian besar responden memiliki persepsi positif terhadap pelaksanaan kurikulum ini. Sebanyak 28,6% menyatakan bahwa pembelajaran IPAS berbasis TI sering memberikan pengalaman belajar yang bermakna, dan 28,6% lainnya menyatakan hal tersebut selalu terjadi. Sementara itu, hanya 14,3% yang menyatakan jarang, dan 14,3% tidak pernah merasakannya. Temuan ini mengindikasikan bahwa penerapan Kurikulum Merdeka berbasis TI mampu menciptakan pengalaman belajar IPAS yang lebih kontekstual, interaktif, dan relevan. Penelitian ini memberikan kontribusi terhadap pengembangan literatur inovasi pendidikan digital di madrasah ibtidaiyah serta memberikan dasar empiris bagi pengambil kebijakan dan pendidik dalam merancang strategi pembelajaran berbasis teknologi.